The Way Things Are: Conversations with Huston Smith on the Spiritual Life - Smith, Huston; Cousineau, Phil (University of California Press, 2003)
"Where can we find what is ultimately meaningful? How can we discover what is truly worth knowing?" In one form or another Huston Smith has been posing these questions to himself--and the world--all his life. In the course of seeking answers, he has become one of the most interesting, enlightening, and celebrated voices on the subject of religion and spirituality throughout the world. The twenty-three interviews and essays in this volume, edited by cultural historian and filmmaker Phil Cousineau, offer a uniquely personal perspective on Smith's own personal journey, as well as wide-ranging reflection on the nature and importance of the religious quest. In The Way Things Are, readers will find Smith in conversation with some of the world's most influential personalities and religious leaders, from journalist Bill Moyers to religion scholar Philip Novak, and recounting his personal experiences with such luminaries as Joseph Campbell, Aldous Huxley, Timothy Leary, Daisetz Suzuki, Ram Dass, and the Dalai Lama. Throughout these engaging exchanges Smith speaks with passion and humor of his upbringing as the son of missionary parents in China, of the inspiring and colorful individuals he has known, and of his impressions of the different religious and philosophical traditions he has encountered. A fascinating view of the state of world religion and religious leadership over the past fifty years, the book also looks to the future with a final interview on the vital importance of the transcendent message of religion for the post-9/11 world. Readers will find The Way Things Are to be Huston Smith's most and accessible book to date.